1998
DOI: 10.1021/jo980356h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition at the Phosphatidylinositol 3,4,5-Trisphosphate-Binding Site. Studies Using the Permuted Isomers of Phosphatidylinositol Trisphosphate

Abstract: Permuted isomers of L-R-phosphatidyl-D-myo-inositol trisphosphate (PtdInsP 3 ), including PtdIns-(3,4,5)P 3 , PtdIns(3,4,6)P 3 , PtdIns(3,5,6)P 3 , and PtdIns(4,5,6)P 3 , have been synthesized as part of our effort to understand the underlying principles governing ligand selection for PtdIns(3,4,5)P 3 -specific binding proteins. These PtdInsP 3 isomers are examined by using two PtdIns(3,4,5)P 3 -dependent functional assays: binding to the C-terminal SH2 domain of the p85 regulatory subunit of PI 3-kinase and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It is especially noteworthy that modification of the flanking Arg 18 and Arg 29 leads to changes in the ligand specificity to PI(4,5)P 2 and PI(3,4)P 2 , respectively. This observation underlines the importance of these two residues in interacting with the 3-and 5-phosphoryl functions on the inositol ring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is especially noteworthy that modification of the flanking Arg 18 and Arg 29 leads to changes in the ligand specificity to PI(4,5)P 2 and PI(3,4)P 2 , respectively. This observation underlines the importance of these two residues in interacting with the 3-and 5-phosphoryl functions on the inositol ring.…”
Section: Discussionmentioning
confidence: 99%
“…were prepared as previously reported (17,18 Preparation of the N-and C-terminal SH2 Domains of the p85 Subunit of PI3K-The pGEX vector containing the cDNA sequence encoding the p85 NT-SH2 domain or the p85 CT-SH2 domain was expressed in Escherichia coli as a GST fusion protein by isopropyl-1-thio-␤-Dgalactopyranoside induction (3). The bacterial lysates were incubated with glutathione-coupled Sepharose 4B beads (Sigma Chemical Co.) for 2 h at 4°C and washed three times with 30 mM Hepes, pH 7.0, containing 100 mM NaCl, 1 mM EDTA, and 0.5% Nonidet P-40, followed by the same buffer without Nonidet P-40 twice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inositol polyphosphates were in part used as conveniently water-soluble analogues of the head groups of phosphoinositides but may also represent physiological ligands. In our opinion this usage of inositol polyphosphates is valid because proteinphosphoinositide interactions appear to be predominantly governed by the charge status, phosphorylation positions, and stereochemistry of the inositol ring (42,44,45). For example, it has been demonstrated that D-Ins (1,4,5)P 3 can functionally replace PtdIns (4, 5)P 2 in the activation of the dynamin GTPase (35) and that the Btk PH domain binds specifically to both D-Ins (1,3,4,5)P 4 and PtdIns (3,4,5)P 3 (35,41) in vitro and to PtdIns (3,4,5)P 3 in vivo (15).…”
Section: Discussionmentioning
confidence: 99%